PSYCHOLOGICAL AND PEDAGOGICAL OPPORTUNITIES FOR DEVELOPING CREATIVITY DURING THE STUDENT PERIOD (Multidisciplinary Journal of Science and Technology, 2026)
The article presents views on the psychological and pedagogical opportunities, conditions, and factors for developing creativity during the student period. In particular, the theoretical analyses of foreign scientists on the manifestation of creativity in the student's personality are described. At the same time, research has been conducted and analyzed to study the formation of creativity during the student period.